Näkökulmia tilintarkastukseen ja arviointiin - Leponiemi, Ulriika; Ruohonen, Janne; Wacker, Jani; Kihn, Lili-Anne; Oulasvirta, Lasse (Tampere University Press, 2017)
This book Näkökulmia tilintarkastukseen ja arviointiin provides original scientific research about various current auditing and evaluation topics. Over the past decade, the field of auditing has seen substantial changes. The topic areas covered in the first chapters reflect established auditing topics such as the role and responsibility of auditors, transfer pricing, the quality of auditing and issues with audit reports. Other chapters address emerging concerns in performance evaluation and auditing. This book will be of value to practitioners, students and academics interested in contemporary aspects of auditing and evaluation.